RECENT TRENDS IN DEPRECIATION DECISIONS. - Mason, Perry (The Accounting Review, 1939)
Abstract The most extensive treatment of depreciation by the U.S. courts has been in the field of public-utility rate regulation; but depreciation has also been considered in other types of cases, including: income tax cases, the determination of corporate income which can be distributed as dividends, the settlement of partnership agreements when the amount of income is in dispute, the life-tenant remainderman situations, master-and-servant cases when a part of the servant's compensation is a share of net income, patent cases when the royalty is a portion of net income, and eminent domain cases in the determination of the value of the confiscated property. In building up an interpretation of depreciation provisions over the years, the courts have proceeded much as the same way; that is, they have attempted to interpret the laws according to accepted practices and standards. Although there is an occasional cross citation, the cases on public-utility rate regulation, in which depredation is involved, seem to constitute a separate group, unrelated to income tax and other types of cases. In the opinion of the author there has been a definite trend in recent years toward the acceptance of complete, systematic depreciation accounting and the recognition of the inevitably close relationship which exists between the periodic allowance and the deduction made in rate-base valuations.